Produção e caracterização funcional de proteína quimérica multiepitópica contendo peptídeos das principais toxinas de aranhas do gênero loxosceles - Sabrina de Almeida Lima (2016)
Spiders from the genus Loxosceles spp show high expression of sphingomyelinases (Smases) and metalloproteinase within its venom glands. Indeed, Smases can reproduce the main symptoms of loxoscelism, whereas metalloproteinases may be involved in hemorrhagic activity. Proteins with hyaluronidasic activity are also present transcripts and are implied in venom spreading. Several studies have shown that antivenoms containing antibodies directed against these proteins are capable of neutralizing in vivo and in vitro the toxic effects of loxoscelic venoms. However, nowadays, antivenom production for therapeutic purposes is limited, due to the fact that great amounts of crude venom is required for immunization and potency tests and, above all, because this immunogen is extremely toxic for the producer animal. For this reason, there is great interest in evaluating possibilities to replace or reduce the amount of crude venom used in antivenom production. In the present study, we have constructed, purified and immunologically characterized a recombinant chimeric protein containing only linear and/or conformational B cell epitopes previously mapped on the three main classes of toxins (SmasesD, metalloproteases and hyaluronidase) present in loxoscelic venom, relevant for human envenomation. The protein produced proved to be non-toxic and induced the production of antibodies with neutralizing potential both in vivo and in vitro.